Enhancing quality Education in Gambian School’s through Digitalization of using Sustainable Technology - Abdoulie Jonga; Sulastri Sulastri (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2026)
The integration of information and communication technology (ICT) in The Gambia’s education system has historically been limited, although recent developments have begun to transform teaching and learning practices. Effective use of ICT is essential for promoting innovative educational approaches that support Sustainable Development Goals (SDGs). This study aims to review and systematize research on innovative strategies that integrate ICT in online learning to promote sustainability in education. The study employs a mixed approach using questionnaire data as the primary source and a comprehensive literature review as the secondary source. The analysis is guided by research questions that examine theoretical and practical perspectives on the relationship between ICT-based educational innovation and sustainable development. The findings highlight key factors influencing the effective use of ICT in educational practice to support the SDGs. The study concludes that digital education plays a significant role in advancing sustainable and innovative learning systems.